Influence of grain boundary structure and topology on the plastic deformation of nanocrystalline aluminum as studied by atomistic simulations. (October 2017) - Prakash, A.; Weygand, D.; Bitzek, E.
Abstract: Nanocrystalline materials, with grain sizes below 100 nm, have been the subject of many research studies in the recent past. At these reduced grain sizes, grain boundaries (GBs) play a very important role in the deformation of such materials. Large scale atomistic simulations that are often used to illuminate the deformation mechanisms in such materials must accurately account for the topology, structure and network of GBs. In this work, we perform atomistic simulations on nanocrystalline aluminum under tensile loading, using a structure with a relaxed GB network obtained from three-dimensional grain growth simulations, and compare the results to that obtained from structures generated using the Voronoi tessellation method. The results show that the grain growth sample results in consistently higher macroscopic stresses when compared to the Voronoi tessellated microstructures. The latter, additionally, tend to overestimate GB deformation, whilst simultaneously underestimating the deformation due to dislocation slip. More importantly, twinning is observed in multiple grains in the grain growth sample, in contrast to the near absence in Voronoi tessellated microstructures. The results are carefully discussed in terms of sample characteristics, stacking fault energies, and GB structure and network. Graphical abstract: Highlights: We study the influence of a relaxed grain boundary network and topology with interface curvature on the deformation behavior of nanocrystalline (NC) aluminum. Large-scale atomistic simulations are performed on samples generated from grain growth simulations, and via Voronoi tessellation. The grain growth sample results in higher peak stresses and higher stresses in the microplastic regime when compared to Voronoi tessellated samples. Voronoi microstructures underestimate the amount of dislocation activity, and overestimate the amount of grain boundary deformation. Relaxed GB network and curvature result in the nucleation of deformation twins, which are generally not observed in Voronoi tessellated microstructures.